High-temperature-resistant UV viscosity-reducing adhesive tape adaptive to various membrane materials, preparation method of high-temperature-resistant UV viscosity-reducing adhesive tape and UV viscosity-reducing adhesive tape

By using high-temperature-resistant UV adhesives prepared by materials such as acrylate polymers, the problem of UV adhesives not durable under high temperature conditions in the prior art is solved, and the adaptation of various film materials and efficient adhesive reduction is achieved. The results improve production efficiency and product quality.

CN119161830APending Publication Date: 2024-12-20JIANGSU SIDIKE NEW MATERIALS SCI & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411211557.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing UV adhesive reducing glue is not durable under high temperature conditions and is easy to fall off or be strongly bonded to the processed materials, resulting in low production efficiency and surface residual glue problems, and it is impossible to adapt to a variety of membrane materials.

Method used

High temperature-resistant UV viscosity-reducing glue composed of acrylate polymers, isocyanate curing agents, multifunctional monomers, vapor phase silica and Japanese hydrochloric acid light diffuser BMSA-18GN are formed through specific preparation methods and combination formulas. High temperature-resistant UV adhesive and UV adhesive tape for a variety of film materials.

Benefits of technology

Provides excellent bonding performance and adhesive reduction effect in high temperature environments, and is suitable for a variety of optical film materials, without residual glue, and improves production efficiency and product yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020435910000151
    Figure BDA0005020435910000151
Patent Text Reader

Abstract

The invention discloses a high-temperature-resistant UV viscosity-reducing adhesive adapted to various membrane materials, a preparation method of the high-temperature-resistant UV viscosity-reducing adhesive and a UV viscosity-reducing adhesive tape. The UV viscosity-reducing adhesive comprises the following raw materials in parts by weight: 100 parts of an acrylate polymer, 0.1-2 parts of an isocyanate curing agent, 0.5-2 parts of a polyfunctional monomer, 0.5-1.5 parts of fumed silica, 0.5-3 parts of a light diffusant, 0.2-0.8 part of an antioxidant, 1-3 parts of a photoinitiator and 50-100 parts of a first solvent. The UV viscosity-reducing adhesive tape disclosed by the invention has excellent adhesive property in a high-temperature environment, and is free from layering and falling off; after high-temperature treatment and standing to the normal temperature, the UV lamp is irradiated to well reduce the viscosity, the viscosity reducing force is smaller than 20 gf, and the method can adapt to various optical film materials (POL, QWP, IQPE and the like) and has no adhesive residue phenomenon, so that the yield of the optical AR film in the processing and manufacturing process is greatly improved, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of UV anti-viscosity adhesive materials, and in particular to a high-temperature resistant UV anti-viscosity adhesive suitable for various film materials, a preparation method thereof and a UV anti-viscosity adhesive tape. Background Art

[0002] With the rapid development of the electronic consumer market, UV viscosity-reducing adhesives are widely used in glass processing and thinning; semiconductor wafer cutting and grinding; AR glasses membrane forming processing and preparation. AR membranes have a high-temperature forming process in a vacuum during the processing process, so a layer of adhesive film with sufficient viscosity and high temperature resistance is required to support plasticity. After the membrane is processed and formed, it is irradiated with UV ultraviolet light to reduce the viscosity, so that it can be easily torn off from the finished membrane. The tearing force is small, less than 20gf, and there is no residual adhesive on the surface after tearing, which does not affect the processing and production of the back-end process. Therefore, there are great requirements for the temperature resistance, viscosity-reducing effect, and adaptability of the UV viscosity-reducing adhesive.

[0003] UV anti-viscosity adhesive usually includes: a substrate, which is the supporting substrate of the UV anti-viscosity film; a pressure-sensitive adhesive, which is an acrylic adhesive, coated on the surface of the substrate; and an isolation layer, which is a release film, attached to the adhesive layer, and is mostly a release film with a PET substrate. The existing UV anti-viscosity adhesive on the market is not heat-resistant during high-temperature processes, and is easy to delaminate with the processing materials POL, QWP, IQPE, etc., causing the material to fall off, affecting production efficiency. (2) Some will also react with optical film POL, QWP, IQPE and other materials during high-temperature processes, making them more firmly bonded. After irradiation with UV ultraviolet light, they cannot be normally anti-viscosity. After being torn off, the surface of the film material is damaged, which greatly reduces the production yield. (3) Better products can reduce viscosity, but after being torn off, there will be residual glue on the surface of the film material, which needs to be wiped off, which increases the production process and production costs. Therefore, it is necessary to develop a high-temperature resistant UV viscosity-reducing adhesive suitable for a variety of film materials (POL, QWP, IQPE). This product is based on this phenomenon and is a high-temperature resistant UV viscosity-reducing protective film that can be adapted to a variety of optical film materials (POL, QWP, IQPE, etc.) with a weight less than 20gf after UV irradiation.

[0004] Therefore, it is necessary to improve the existing technology to provide a more reliable solution. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a high temperature resistant UV viscosity reducing adhesive suitable for a variety of film materials, a preparation method thereof and a UV viscosity reducing adhesive tape in view of the deficiencies in the above-mentioned prior art.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: in the first aspect of the present invention, a high temperature resistant UV viscosity reducing adhesive suitable for a variety of film materials is provided, comprising the following raw materials in parts by weight:

[0007] 100 parts of acrylate polymer, 0.1-2 parts of isocyanate curing agent, 0.5-2 parts of multifunctional monomer, 0.5-1.5 parts of fumed silica, 0.5-3 parts of light diffusing agent, 0.2-0.8 parts of antioxidant, 1-3 parts of photoinitiator, and 50-100 parts of first solvent.

[0008] Preferably, the acrylic ester polymer is prepared from the following raw material components calculated by weight:

[0009] 75-85 parts of soft monomer, 10-20 parts of hard monomer, 5-20 parts of multifunctional monomer, 0.1-1 parts of initiator, 0.05-0.2 parts of inhibitor, 15-20 parts of grafting monomer, and 100-200 parts of second solvent.

[0010] Preferably, the soft monomer is one or more of alkyl acrylate monomers;

[0011] The hard monomer is one or more of alkyl acrylate and alkyl methacrylate having a glass transition temperature greater than -30°C;

[0012] The multifunctional monomer is an acrylic monomer containing carboxyl, amide and hydroxyl groups.

[0013] Preferably, the initiator is an azo or peroxide initiator;

[0014] The polymerization inhibitor is at least one of hydroquinone, p-hydroxyanisole and cyclopentyl methyl ether;

[0015] The grafting monomer is one or more of isocyanoethyl methacrylate (MOI), isocyanate ethyl acrylate (AOI), isocyanate acrylate, and isocyanoethyl acrylate;

[0016] The first solvent is one or more of ethyl acetate, toluene and butanone.

[0017] Preferably, the acrylic acid ester polymer is prepared by the following method:

[0018] Add part of the soft monomer, part of the hard monomer, part of the multifunctional monomer and part of the first solvent into a reaction container, and pass nitrogen gas for 20-40 minutes under stirring at 70° C., and dropwise add part of the initiator and the remaining soft monomer, the remaining hard monomer and the remaining functional monomer into the reaction container under nitrogen environment, and complete the dropwise addition in two hours, and then react for another 2 hours, and then add the remaining initiator, and keep reacting for 2-6 hours to obtain a first mixture;

[0019] Air was introduced into the first mixture for half an hour, and an inhibitor and the remaining first solvent were added. Then, the grafted monomer was added dropwise at 70° C. The addition was completed within 1 hour, and the reaction was continued at 70° C. for 3 hours to obtain an acrylate polymer.

[0020] Preferably, the isocyanate curing agent is one or more of diisocyanates such as toluene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, 4,4-diphenylmethane diisocyanate, and isophorone diisocyanate curing agent;

[0021] The multifunctional monomer is one or more of unsaturated polyester resin, polyurethane resin, epoxy acrylic resin, and polyether acrylic resin;

[0022] The antioxidant is a phenolic antioxidant;

[0023] The photoinitiator is one or more of an acetophenone photoinitiator, a benzoin photoinitiator, a benzophenone photoinitiator, a thioxanthone photoinitiator, and an acylphosphine oxide photoinitiator;

[0024] The second solvent is one or more of ethyl acetate, toluene and butanone.

[0025] Preferably, the fumed silica is selected from LM150 of Dalian Liansheng Trading Co., Ltd.;

[0026] The light diffuser is selected from one or more of the light diffusers sold by Sekisui Japan, including SBX series, EXM series, MBX series, MS10X8D, ISMX-8M, and BMSA-18GN.

[0027] The second aspect of the present invention provides a method for preparing a high-temperature resistant UV viscosity-reducing adhesive that is compatible with a variety of film materials as described above, comprising the following steps: in parts by weight, 100 parts of an acrylate polymer, 0.1 to 2 parts of an isocyanate curing agent, 0.5 to 2 parts of a multifunctional monomer, 0.5 to 1.5 parts of fumed silica, 0.5 to 3 parts of a light diffuser, 0.2 to 0.8 parts of an antioxidant, 1 to 3 parts of a photoinitiator, and 50 to 100 parts of a first solvent are stirred evenly to obtain the high-temperature resistant UV viscosity-reducing adhesive that is compatible with a variety of film materials.

[0028] The third aspect of the present invention provides a high-temperature resistant UV anti-viscosity tape that is compatible with a variety of film materials, which is prepared by the following method: the high-temperature resistant UV anti-viscosity adhesive that is compatible with a variety of film materials as described above is evenly coated on a substrate, dried at 110-130°C for 3-5 minutes, the adhesive surface is attached to a release film, and then matured to obtain the high-temperature resistant UV anti-viscosity tape that is compatible with a variety of film materials.

[0029] Preferably, the substrate is a PET film with a thickness of 25-100 μm.

[0030] The beneficial effects of the present invention are:

[0031] The present invention provides a high-temperature resistant UV viscosity-reducing adhesive and tape product that is compatible with a variety of film materials. The UV viscosity-reducing tape of the present invention has excellent bonding performance in a high-temperature environment and will not delaminate or fall off. After high-temperature treatment and then standing to room temperature, irradiation with a UV lamp can effectively reduce the viscosity, and the viscosity-reducing force is less than 20gf. The adhesive can be compatible with a variety of optical film materials (POL, QWP, IQPE, etc.) and has the characteristic of no residual adhesive, which greatly improves the yield of optical AR films in processing and manufacturing and increases production efficiency.

[0032] The present invention introduces high temperature resistant resin and inorganic gas silica (fumed silica) into the UV viscosity reducing adhesive. Generally, the addition of high temperature resistant resin can give the adhesive film a certain temperature resistance, but the effect is general. The addition of gas silica greatly improves the temperature resistance of the adhesive film, provides good adhesion in a high temperature environment, can ensure the processing and manufacturing of the film material, and at the same time enables the adhesive film to be adapted to a variety of substrates and can reduce viscosity normally. The present invention also adds Japan Sekisui light diffuser BMSA-18GN into the UV viscosity reducing adhesive. This auxiliary agent is evenly dispersed and suspended on the surface of the adhesive layer. It can be particularly targeted at POL and other attached objects, because the POL surface double bond content is relatively high, and the light diffuser BMSA-18GN particles greatly reduce the contact between the double bonds inside the adhesive film and the double bonds of the attached object, which can avoid their reaction, so that the adhesive film can be treated at high temperature, then allowed to stand to room temperature, and then irradiated by UV lamp to achieve good viscosity reduction. DETAILED DESCRIPTION

[0033] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0034] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0035] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0036] The present invention provides a high temperature resistant UV viscosity reducing adhesive suitable for various film materials, comprising the following raw materials in parts by weight:

[0037] 100 parts of acrylate polymer, 0.1-2 parts of isocyanate curing agent, 0.5-2 parts of multifunctional monomer, 0.5-1.5 parts of fumed silica, 0.5-3 parts of light diffusing agent, 0.2-0.8 parts of antioxidant, 1-3 parts of photoinitiator, and 50-100 parts of first solvent.

[0038] In a preferred embodiment, the acrylate polymer is prepared from the following raw material components calculated by weight:

[0039] 75-85 parts of soft monomer, 10-20 parts of hard monomer, 5-20 parts of multifunctional monomer, 0.1-1 parts of initiator, 0.05-0.2 parts of inhibitor, 15-20 parts of grafting monomer, and 100-200 parts of second solvent.

[0040] In a preferred embodiment, the soft monomer is one or more of alkyl acrylate monomers (including ethyl, propyl, butyl, pentyl, heptyl, octyl, nonyl, decyl, polyalkyl and isomers thereof); more preferably, it is an alkyl acrylate monomer having more than 8 carbon atoms.

[0041] In a preferred embodiment, the hard monomer is one or more of alkyl acrylates and alkyl methacrylates having a glass transition temperature greater than -30°C; more preferably, one or more of methyl acrylate, methyl methacrylate, glycidyl methacrylate, and isooctyl methacrylate.

[0042] The multifunctional monomer is an acrylic monomer containing a carboxyl group, an amide group, or a hydroxyl group, and more preferably is one or more of hydroxyethyl acrylate, hydroxybutyl acrylate, hydroxypropyl acrylate, acrylic acid, acrylamide, and 4-acryloylmorpholine.

[0043] In a preferred embodiment, the initiator is an azo or peroxide initiator; more preferably, it is one or more of azobisisoheptanenitrile, azobisisobutyronitrile, dimethyl azobisisobutyrate, and dibenzoyl peroxide.

[0044] In a preferred embodiment, the polymerization inhibitor is at least one of hydroquinone, p-hydroxyanisole, and cyclopentyl methyl ether.

[0045] In a preferred embodiment, the grafting monomer is one or more of isocyanoethyl methacrylate (MOI), isocyanate ethyl acrylate (AOI), isocyanate acrylate, and isocyanoethyl acrylate;

[0046] The first solvent is one or more of ethyl acetate, toluene and butanone.

[0047] In a preferred embodiment, the acrylate polymer is prepared by the following method:

[0048] Add part of the soft monomer, part of the hard monomer, part of the multifunctional monomer and part of the first solvent into a reaction container, and pass nitrogen gas for 20-40 minutes under stirring at 70° C., and dropwise add part of the initiator and the remaining soft monomer, the remaining hard monomer and the remaining functional monomer into the reaction container under nitrogen environment, and complete the dropwise addition in two hours, and then react for another 2 hours, and then add the remaining initiator, and keep reacting for 2-6 hours to obtain a first mixture;

[0049] Air was introduced into the first mixture for half an hour, and an inhibitor and the remaining first solvent were added. Then, the grafted monomer was added dropwise at 70° C. The addition was completed within 1 hour, and the reaction was continued at 70° C. for 3 hours to obtain an acrylate polymer.

[0050] In a preferred embodiment, the isocyanate curing agent is one or more of diisocyanates such as toluene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, 4,4-diphenylmethane diisocyanate, and isophorone diisocyanate curing agent.

[0051] In a preferred embodiment, the multifunctional monomer is one or more of unsaturated polyester resin, polyurethane resin, epoxy acrylic resin, and polyether acrylic resin; specific examples of commercially available multifunctional monomers include: BOMAR series from DYMAX: BRS-14320S, BR-3747AE, BR-371MS, BR-3641AJ, BR-3641AA, BDT-1015, BR-952, BR-941, etc., more preferably BR-941.

[0052] In a preferred embodiment, the antioxidant is a phenolic antioxidant; more preferably, it is one or more of 1130, 1010, 168.

[0053] A photoinitiator (photopolymerization initiator) refers to a compound that decomposes by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, etc. to generate free radical species, cationic species, or anionic species. The photoinitiator is one or more of an acetophenone-based photoinitiator, a benzoin-based photoinitiator, a benzophenone-based photoinitiator, a thioxanthone-based photoinitiator, and an acylphosphine oxide-based photoinitiator.

[0054] Examples of the acetophenone-based photoinitiator include, but are not limited to, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, benzil dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-morpholino(4-thiomethylphenyl)propane-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)butanone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomers. For example, commercially available photoinitiators such as 2,4,6-trimethylbenzoyl (TPO), 1-hydroxycyclohexyl phenyl ketone (184), phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide (819), 2-hydroxy-2-methyl-1-phenyl-1-propanone (1173), and dibenzoyl (651) can be used.

[0055] In a preferred embodiment, the second solvent is one or more of ethyl acetate, toluene, and butanone.

[0056] In a preferred embodiment, the fumed silica is selected from LM150 of Dalian Liansheng Trading Co., Ltd.

[0057] In a preferred embodiment, the light diffuser is selected from one or more of the light diffusers sold by Sekisui Japan, namely, SBX series, EXM series, MBX series, MS10X8D, ISMX-8M, and BMSA-18GN.

[0058] The present invention also provides a method for preparing the high-temperature resistant UV viscosity-reducing adhesive suitable for a variety of film materials as above, comprising the following steps: by weight, 100 parts of acrylate polymer, 0.1-2 parts of isocyanate curing agent, 0.5-2 parts of multifunctional monomer, 0.5-1.5 parts of fumed silica, 0.5-3 parts of light diffuser, 0.2-0.8 parts of antioxidant, 1-3 parts of photoinitiator, and 50-100 parts of a first solvent are stirred evenly to obtain a high-temperature resistant UV viscosity-reducing adhesive suitable for a variety of film materials.

[0059] The present invention also provides a high-temperature resistant UV anti-viscosity tape suitable for a variety of film materials, which is prepared by the following method: the high-temperature resistant UV anti-viscosity adhesive suitable for a variety of film materials as above is evenly coated on a substrate, dried at 110-130°C for 3-5 minutes, the adhesive surface is attached to a release film, and then matured to obtain a high-temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0060] In a preferred embodiment, the substrate is a PET film with a thickness of 25-100 μm.

[0061] The release film is used as an isolation layer of the adhesive surface. In a preferred embodiment, a release film with PET as the base material is selected, and the thickness is preferably 25-100 μm, and more preferably 50 μm.

[0062] In view of the problems existing in traditional UV anti-viscosity protective films, the present invention introduces high-temperature resistant resin and inorganic gas silica (fumed silica) into the compounded UV anti-viscosity adhesive. Generally, the addition of high-temperature resistant resin can give the film a certain temperature resistance, but the effect is general. The addition of gas silica greatly improves the temperature resistance of the film, provides good adhesion in high temperature environment, ensures the processing and manufacturing of the film material, and at the same time enables the film to adapt to a variety of substrates and can reduce viscosity normally. In the present invention, a Japanese Sekisui light diffuser (BMSA-18GN in a preferred embodiment) is further added to the UV viscosity-reducing adhesive. After being evenly dispersed, the additive is suspended on the surface of the adhesive layer, especially for POL, because the surface content of POL is relatively high, and the light diffuser BMSA-18GN particles greatly reduce the contact between the double bonds inside the adhesive film and the double bonds of the adhered object, thereby avoiding their reaction, so that the adhesive film can be allowed to stand at room temperature after high temperature, and can be well de-vised after being irradiated by a UV lamp. After irradiation with a UV ultraviolet lamp, the peeling force is less than 20gf, and it can be well torn off, and there is no residual adhesive on the surface after torn off, which can greatly improve production efficiency.

[0063] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0064] Example 1

[0065] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0066] S1. Preparation of acrylic acid ester polymer:

[0067] Into a reaction kettle were added 50 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of 4-acryloylmorpholine, 4 parts by weight of hydroxyethyl acrylate, 2 parts by weight of glycidyl methacrylate, 15 parts by weight of toluene and 80 parts by weight of ethyl acetate. The temperature was raised to 70° C., nitrogen was passed through and stirred for 30 minutes, 0.3 parts by weight of azobisisobutyronitrile, 27 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of 4-acryloylmorpholine, 4 parts by weight of hydroxyethyl acrylate and 3 parts by weight of glycidyl methacrylate were mixed and added dropwise to the reactor for two hours, followed by further reaction for 2 hours, 0.1 parts by weight of azobisisobutyronitrile was added, and the reaction was maintained for 4 hours to obtain a first mixture; air was passed through the first mixture for half an hour, 0.05 parts by weight of inhibitor MEHQ and 90 parts by weight of ethyl acetate were added, stirred for 10 minutes, and then a mixture of 19 parts by weight of ethyl isocyanate acrylate (AOI) and 40 parts by weight of ethyl acetate was added at 70° C. for 1 hour, and finally grafting was continued at 70° C. for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0068] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 1 part of gas silicone LM150, 1 part of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 0.9 parts of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0069] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0070] Example 2

[0071] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0072] S1. Preparation of acrylic acid ester polymer:

[0073] Put 50 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, 20 parts by weight of 2-ethylhexyl acrylate, 5 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 90 parts by weight of ethyl acetate, stir for 10 minutes, then add 19 parts by weight of isocyanate ethyl acrylate (AOI) and 40 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0074] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 0.5 parts of gas silicone LM150, 0.5 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 0.9 parts of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0075] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0076] Example 3

[0077] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0078] S1. Preparation of acrylic acid ester polymer:

[0079] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate and 100 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate and 5 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours to obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ and 55 parts by weight of ethyl acetate, stir for 10 minutes, then add 19 parts by weight of isocyanate ethyl acrylate (AOI) and 30 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0080] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 1.5 parts of gas silicone LM150, 2 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 0.9 parts of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive.

[0081] The evenly stirred mixture was coated on a 50 μm PET film, the dry glue thickness was controlled to be 20 μm, baked in an oven at 120°C for 3 min, laminated to a 50 μm release film, and aged at 70°C for 1 day to obtain a high-temperature resistant UV-resistant adhesive tape suitable for a variety of film materials.

[0082] Example 4

[0083] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0084] S1. Preparation of acrylic acid ester polymer:

[0085] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 100 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 50 parts by weight of ethyl acetate, stir for 10 minutes, then add a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 30 parts by weight of ethyl acetate at 70°C for 1 hour, and finally continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0086] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 0.8 parts of multifunctional monomer BR-941, 1 part of gas silicone LM150, 3 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 1 part of photoinitiator TPO are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0087] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0088] Example 5

[0089] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0090] S1. Preparation of acrylic acid ester polymer:

[0091] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 15 parts by weight of ethyl acetate, stir for 10 minutes, then drip a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 70 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0092] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 1 part of gas silicone LM150, 2 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 1 part of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0093] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0094] Comparative Example 1

[0095] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0096] S1. Preparation of acrylic acid ester polymer:

[0097] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 15 parts by weight of ethyl acetate, stir for 10 minutes, then drip a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 70 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0098] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 1 part of gas silicone LM150, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 1 part of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0099] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0100] Comparative Example 2

[0101] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0102] S1. Preparation of acrylic acid ester polymer:

[0103] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 15 parts by weight of ethyl acetate, stir for 10 minutes, then drip a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 70 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0104] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 3 parts of multifunctional monomer BR-941, 1 part of gas silicone LM150, 2 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 1 part of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0105] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0106] Comparative Example 3

[0107] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0108] S1. Preparation of acrylic acid ester polymer:

[0109] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, the remaining 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 15 parts by weight of ethyl acetate, stir for 10 minutes, then drip a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 70 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0110] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 0 parts of multifunctional monomer BR-941, 1 part of gas silicone LM150, 2 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 1 part of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0111] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0112] Comparative Example 4

[0113] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0114] S1. Preparation of acrylic acid ester polymer:

[0115] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, the remaining 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 15 parts by weight of ethyl acetate, stir for 10 minutes, then drip a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 70 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0116] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 0.5 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 0.9 parts of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0117] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0118] Comparative Example 5

[0119] A high temperature resistant UV adhesive tape suitable for a variety of film materials is prepared by the following method:

[0120] S1. Preparation of acrylic acid ester polymer:

[0121] Put 14 parts by weight of 2-ethylhexyl acrylate, 4 parts by weight of 4-acryloylmorpholine, 5 parts by weight of hydroxyethyl acrylate, and 80 parts by weight of ethyl acetate into a reactor. Heat to 70°C, stir for 30 minutes with nitrogen, add 0.3 parts by weight of azobisisobutyronitrile, the remaining 51 parts by weight of 2-ethylhexyl acrylate, 11 parts by weight of 4-acryloylmorpholine, 15 parts by weight of hydroxyethyl acrylate, and 10 parts by weight of ethyl acetate to the reactor, drip for two hours, then react for another 2 hours, add 0.1 parts by weight of azobisisobutyronitrile, keep reacting for 4 hours, and obtain a first mixture; introduce air into the first mixture for half an hour, add 0.05 parts by weight of inhibitor MEHQ, 15 parts by weight of ethyl acetate, stir for 10 minutes, then drip a mixture of 19 parts by weight of isocyanate ethyl acrylate (AOI) and 70 parts by weight of ethyl acetate at 70°C for 1 hour, and continue grafting at 70°C for 3 hours to obtain an acrylate polymer with a weight average molecular weight Mw of 50-60w.

[0122] S2. By weight, 100 parts of acrylic polymer, 0.2 parts of toluene diisocyanate, 1.5 parts of multifunctional monomer BR-941, 1 part of silica particles (20 nm Borfos-SiO2-820, purchased from Bohuasi Nanotechnology), 0.5 parts of light diffuser BMSA-18GN, 0.4 parts of antioxidant 1010, 0.6 parts of photoinitiator 1173 and 0.9 parts of photoinitiator 184 are uniformly mixed to obtain a high temperature resistant UV viscosity reducing adhesive;

[0123] The high temperature resistant UV anti-viscosity adhesive was coated on a 50 μm PET film, the dry adhesive thickness was controlled to be 20 μm, and the film was baked in an oven at 120°C for 3 min. The adhesive surface was attached to a 50 μm PET release film and aged at 70°C for 1 day to obtain a high temperature resistant UV anti-viscosity tape suitable for a variety of film materials.

[0124] The samples prepared in the embodiments and comparative examples were subjected to a peeling force test. The test method was as follows: the UV anti-adhesion film sample was cut into samples with a width of 25.4 mm and a length of 300 mm. The release film was peeled off and rolled onto the adhered object (QWP) with a 2KG roller at a speed of 600MM / MIN. The sample was allowed to stand for 20 minutes and its 180° peeling adhesion was tested using a tensile testing machine. The specific test method was based on the ASMTD3330 international standard.

[0125] The test results are shown in Table 1 below:

[0126] Table 1

[0127]

[0128] According to the test results in Table 1, it can be explained that:

[0129] From Examples 1-5, it can be seen that the UV anti-viscosity film prepared by adding gas silicon has good adhesion at high temperature. By adjusting the amount of light dispersant added, it is found that 2 parts of anti-viscosity is the best, and it can be adapted to a variety of optical film materials. By verifying the type of photoinitiator, it is found that the combination of 1173 and 184 at a ratio of 3:5 has the best effect.

[0130] Compared with Example 5, Comparative Example 1 did not add a light diffuser, and it was found that the addition of a light diffuser had a very good effect on reducing the viscosity of the entire film; Compared with Example 5, the amount of multifunctional resin was adjusted in Comparative Examples 2 and 3, and the amount of multifunctional monomer was also very particular. Without adding, the overall viscosity of the film was reduced, and the adhesion to the plate was insufficient. If there was too much, there would be precipitation after baking when bonding optical film materials (POL, QWP, IQPE, etc.), so adding a suitable amount can solve this difficulty. Compared with Example 1, Comparative Examples 4 and 5 can be seen that the addition of gas silicon has a great effect on the improvement of the high-temperature viscosity of the product, and compared with silica particles, gas silicon has a better improvement in product performance.

[0131] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A high temperature resistant UV viscosity reducing adhesive suitable for a variety of membrane materials, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of acrylate polymer, 0.1-2 parts of isocyanate curing agent, 0.5-2 parts of multifunctional monomer, 0.5-1.5 parts of fumed silica, 0.5-3 parts of light diffusing agent, 0.2-0.8 parts of antioxidant, 1-3 parts of photoinitiator, and 50-100 parts of first solvent.

2. The high temperature resistant UV viscosity reducing adhesive suitable for various membrane materials according to claim 1, characterized in that: The acrylic acid ester polymer is prepared from the following raw material components calculated by weight: 75-85 parts of soft monomer, 10-20 parts of hard monomer, 5-20 parts of multifunctional monomer, 0.1-1 parts of initiator, 0.05-0.2 parts of inhibitor, 15-20 parts of grafting monomer, and 100-200 parts of second solvent.

3. The high temperature resistant UV viscosity reducing adhesive suitable for various membrane materials according to claim 2, characterized in that: The soft monomer is one or more of alkyl acrylate monomers; The hard monomer is one or more of alkyl acrylate and alkyl methacrylate having a glass transition temperature greater than -30°C; The multifunctional monomer is an acrylic monomer containing carboxyl, amide and hydroxyl groups.

4. The high temperature resistant UV viscosity reducing adhesive suitable for various membrane materials according to claim 2, characterized in that: The initiator is an azo or peroxide initiator; The polymerization inhibitor is at least one of hydroquinone, p-hydroxyanisole and cyclopentyl methyl ether; The grafting monomer is one or more of isocyanoethyl methacrylate, isocyanate ethyl acrylate, isocyanate acrylate, and isocyanoethyl acrylate; The first solvent is one or more of ethyl acetate, toluene and butanone.

5. The high temperature resistant UV viscosity reducing adhesive suitable for various membrane materials according to claim 2, characterized in that: The acrylic acid ester polymer is prepared by the following method: Add part of the soft monomer, part of the hard monomer, part of the multifunctional monomer and part of the first solvent into a reaction container, and pass nitrogen gas for 20-40 minutes under stirring at 70° C., and dropwise add part of the initiator and the remaining soft monomer, the remaining hard monomer and the remaining functional monomer into the reaction container under nitrogen environment, and complete the dropwise addition in two hours, and then react for another 2 hours, and then add the remaining initiator, and keep reacting for 2-6 hours to obtain a first mixture; Air was introduced into the first mixture for half an hour, and an inhibitor and the remaining first solvent were added. Then, the grafted monomer was added dropwise at 70° C. The addition was completed within 1 hour, and the reaction was continued at 70° C. for 3 hours to obtain an acrylate polymer.

6. The high temperature resistant UV viscosity reducing adhesive suitable for various membrane materials according to claim 1, characterized in that: The isocyanate curing agent is one or more of toluene diisocyanate, hexamethylene diisocyanate, diphenylmethane diisocyanate, 4,4-diphenylmethane diisocyanate and other diisocyanates, and isophorone diisocyanate curing agent; The multifunctional monomer is one or more of unsaturated polyester resin, polyurethane resin, epoxy acrylic resin, and polyether acrylic resin; The antioxidant is a phenolic antioxidant; The photoinitiator is one or more of an acetophenone photoinitiator, a benzoin photoinitiator, a benzophenone photoinitiator, a thioxanthone photoinitiator, and an acylphosphine oxide photoinitiator; The second solvent is one or more of ethyl acetate, toluene and butanone.

7. The high temperature resistant UV viscosity reducing adhesive suitable for various membrane materials according to claim 1, characterized in that: The fumed silica is selected from LM150 of Dalian Liansheng Trading Co., Ltd.; The light diffuser is selected from one or more of the light diffusers sold by Sekisui Japan, including SBX series, EXM series, MBX series, MS10X8D, ISMX-8M, and BMSA-18GN.

8. A method for preparing a high temperature resistant UV viscosity reducing adhesive suitable for a variety of film materials as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing 100 parts by weight of an acrylate polymer, 0.1 to 2 parts of an isocyanate curing agent, 0.5 to 2 parts of a multifunctional monomer, 0.5 to 1.5 parts of fumed silica, 0.5 to 3 parts of a light diffuser, 0.2 to 0.8 parts of an antioxidant, 1 to 3 parts of a photoinitiator and 50 to 100 parts of a first solvent, and uniformly stirring the mixture to obtain the high temperature resistant UV viscosity reducing adhesive suitable for a variety of film materials.

9. A high temperature resistant UV adhesive tape suitable for a variety of membrane materials, characterized in that: The method is as follows: the high temperature resistant UV anti-viscosity adhesive suitable for a variety of film materials as described in any one of claims 1 to 7 is evenly coated on a substrate, dried at 110-130°C for 3-5 minutes, the adhesive surface is attached to a release film, and then aged to obtain the high temperature resistant UV anti-viscosity adhesive tape suitable for a variety of film materials.

10. The high temperature resistant UV adhesive tape suitable for various membrane materials according to claim 9, characterized in that: The substrate is a PET film with a thickness of 25-100 μm.

Citation Information

Patent Citations

  • Acrylate polymer with high deformation quantity, OCA (Optical Clear Adhesive) and adhesive film

    CN116874658A

  • UV (ultraviolet) visbreaking protective film

    CN116948556A

  • UV viscosity-reducing adhesive, protective film for glass sand blasting and preparation method of protective film

    CN117210140A

  • High-temperature-resistant acrylate polymer, OCA optical adhesive and adhesive film

    CN117510751A

  • Adhesive composition

    WO2019245246A1